Investigation of indentation size effect (ISE) and micro-mechanical properties of Lu added Bi2Sr2CaCu2Oy ceramic superconductors - Öztürk, Özgür; Erdem, M.; Aşıkuzun, Elif; Yıldız, O.; Yıldırım, Gürcan; Varilci, Ahmet; Terzioğlu, Cabir (Springer Science and Business Media LLC, 2012)
In this study, we investigated the effect of the Lutetium (Lu) addition on microstructure and mechanical properties of the Bi-2212 superconductors annealed at 840 °C for 50 h. The samples were prepared by the widely used conventional solid-state reaction method. For comparison, undoped sample was prepared in the same conditions. The prepared samples were characterized using X-ray powder diffraction (XRD), scanning electron microscope (SEM), and microhardness measurements (Hv). The volume fraction and lattice parameters were determined from the XRD measurements. The microstructure, surface morphology and orientation of the grains were investigated by SEM. In this study we have focused on microhardness measurements to investigate the mechanical properties. Vickers microhardness, load independent hardness, Young’s modulus, fracture toughness and yield strength values were calculated separately for doped and undoped samples. Experimental results of hardness measurements were analyzed using the Meyer’s law, proportional sample resistance (PSR)model, modified proportional sample resistance (MPRS) model, Elastic–Plastic deformation model (EPD), and Hays-Kendall (HK) approach. Finally, the Hays-Kendall (HK) approach was determined as the most successful model describing the mechanical properties of our samples. Moreover, lattice parameter c and volume fraction of Bi-2212 phase decreased with increasing Lu content. SEM measurements show that not only the surface morphology and grain connectivity were obtained to degrade but also the grain sizes of the samples were found to decrease with the increase of the Lu addition, as well.